Analysis of leachate quality data from selected sanitary landfills in northern Philippines - De Ramos, Ana Renee M. (2012)
The production and management of leachate are recognized as some of the major problems associated with the operation of sanitary landfills. In this research, four landfills were studied to better understand the characteristics of leachates. Secondary data were obtained from these landfills but only two landfills were sampled for actual leachate analysis. Landfill A is a closed landfill and landfills B, C, and D are active. Parameters investigated in this research include pH, color, BOD5, COD, TSS, Oil and Grease, and metals and toxic substances. (As, Hg, Cd, CR+6, Pb, and Free Cyanide). The results indicated the baseline data for sanitary landfills in Northern Philippines and are presented as concentration range per parameter. The pH values generally range from 6.52 to 9.56 while color varies from 20 to 12,500 PCU. BOD5 values fall in the range of 11 to 23,600 mg/L, while COD values range between 30 to 62,400 mg/L. the BOD5/COD ratio of Site C, which is 0.5, suggests that it is a young and unstable landfill while the BOD5/COD ratio of site B, which is 0.424, reveals that Site B is a moderately stable landfill. The TSS concentrations are from 2 to 3,840 mg/L and Oil and Grease values fall between 0.65 to 10 mg/L. Low heavy metal concentrations are observed due to high pH values which inhibit metal solubilization in leachates. The Total Cadmium values obtained from this study are below detection limits. Poisson's distribution confirms that the concentrations for the total As, Total Hg, Hexavalent Chromium and Total Pb fall within the range of Not Detected (ND) to 0.23 mg/L, ND to 5.93 mg/L, ND to 0.096 and ND to 0.196 mg/L, respectively. The Free Cyanide values fall within the range of ND to 116 mg/L. All the parameters exhibited a shift towards methanogenic activity characteristics within one year after waste disposition.